Green growth is a pathway to sustainable development: An empirical study of Saudi Green Initiative - Alajmi, Reema (Journal of Economics and Administrative Sciences, 2025)
For climate change adaptation and mitigation, a sustainable transition to green growth is essential. The aim of this study is to evaluate green growth indicators using three methods to assess the situation of green growth in Saudi Arabia. The vector error correction model (VECM) was used to estimate the relationship between electricity generation and carbon emissions (CO2), and then examine the mitigation scenario, followed by analysing Saudi green growth indicators versus Organisation for Economic Co-operation and Development (OECD) indicators. The results indicate carbon emissions are influenced by the GDP and electricity generation in Saudi Arabia. Environmental scenarios findings indicate that the baseline scenario (BAU) result shows that carbon emissions from 2021 to 2030 will continue rising, while the scenario 1 result implies that Saudi Arabia’s carbon emissions will decrease from 2021 to 2030. In addition, it analyses the green growth indicators for Saudi Arabia, comparing Saudi initiatives with OECD green growth indicators to explore if these actions align. After reviewing Saudi Arabia’s green initiatives, Saudi is in alignment with OECD indicators. Finally, the study highlights some policies which could help the country achieve its initiatives and reach zero carbon emissions. Thus, this study contributes to the literature by evaluating the effect of green growth initiatives represented in energy abatement policies on CO2 emissions to explore if it is consistent with the Paris Agreement and NDC.